2007
DOI: 10.1016/j.pain.2007.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of catastrophizing in sickle cell disease – The PiSCES project

Abstract: In several types of chronic pain, catastrophizing has been related to higher pain intensity, and health care utilization but it has not been explored extensively in sickle cell disease (SCD). The objective of the study was to identify the role of catastrophizing in SCD, specifically in relation to painful crises, non-crisis pain, and responses to pain. Two hundred and twenty SCD adults were enrolled in a prospective cohort study of pain and completed between 30 and 188 daily diaries in 6 months. The Catastroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 38 publications
1
46
1
Order By: Relevance
“…This suggests that prior findings that SCD patients tend to catastrophize more than other chronic pain patients [7] may be driven by a number of disease-related factors that deserve future investigation. The nature of SCD pain as related to a life-long and life-threatening disease may promote disease-related catastrophizing.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This suggests that prior findings that SCD patients tend to catastrophize more than other chronic pain patients [7] may be driven by a number of disease-related factors that deserve future investigation. The nature of SCD pain as related to a life-long and life-threatening disease may promote disease-related catastrophizing.…”
Section: Discussionmentioning
confidence: 91%
“…However, this elevated catastrophizing is not associated with heightened crisis or non-crisis pain intensity, distress, or pain-related interference when symptoms of depression are controlled [7]. Therefore, others have concluded that inferences about catastrophizing and pain drawn from other populations should not be translated to sickle cell pain [7]. …”
Section: Introductionmentioning
confidence: 99%
“…1,7,21,23,26,48 PiSCES was a cohort study measuring the variability in pain and response to pain in 308 patients with SCD, 16 years of age and older. Data were collected between 2001 and 2006 from patients recruited from multiple clinical settings.…”
Section: Methodsmentioning
confidence: 99%
“…51 We found that SCD subjects had higher mean catastrophizing scores than those found in studies of other chronic pain conditions that are not lifelong or life-threatening. 52 Two recent studies advanced the understanding of the impact of depression on pain. 53,54 The latter study found that depressed subjects had pain on significantly more days than non-depressed subjects.…”
Section: Psychological Predictorsmentioning
confidence: 99%
“…When in pain on non-crisis days, depressed subjects had higher mean pain, higher distress from pain, and more interference from pain. 52 Over two decades ago, coping strategies among SCD adults were found to be important predictors of pain and adjustment. Individuals with high scores on the negative thinking and passive adherence categories had more severe pain, were less active and more distressed, and used more health care services.…”
Section: Psychological Predictorsmentioning
confidence: 99%